2002
DOI: 10.1002/hyp.1181
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible sorption of benzene in sandy aquifer materials

Abstract: Abstract:Hydrocarbon compounds in aquifers are generally known to show a retardation effect due to sorption onto the surfaces of solid particles. In this study, we investigated the effect of sorption on the transport of benzene in sandy aquifer materials by conducting batch and column tests for both sandy aquifer materials and sandy materials to which had been added 0Ð5% powdered activated carbon. The batch test was conducted by equilibrating dry materials with benzene solutions of various initial concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
4
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
1
24
4
1
Order By: Relevance
“…These values are considerably different from the results of Priddle and Jackson (1991), who reported from a laboratory column experiment that benzene was retarded 14Ð3 times relative to a conservative tracer. However, they were slightly overestimated compared to the results of Baek et al (2003), who found that no benzene retardation occurred during transport through sandy aquifer materials. Despite the same aquifer materials being used in the two laboratory aquifer model tests, the discrepancy between the results from this study and Baek et al (2003) can be attributed to the effect of flow velocity on the benzene retardation.…”
Section: Retardation Of Benzene Plumecontrasting
confidence: 62%
See 3 more Smart Citations
“…These values are considerably different from the results of Priddle and Jackson (1991), who reported from a laboratory column experiment that benzene was retarded 14Ð3 times relative to a conservative tracer. However, they were slightly overestimated compared to the results of Baek et al (2003), who found that no benzene retardation occurred during transport through sandy aquifer materials. Despite the same aquifer materials being used in the two laboratory aquifer model tests, the discrepancy between the results from this study and Baek et al (2003) can be attributed to the effect of flow velocity on the benzene retardation.…”
Section: Retardation Of Benzene Plumecontrasting
confidence: 62%
“…Mass reduction of hydrocarbon compounds by volatilization was also reported by Chiang et al (1989) and Lahvis et al (1999), who observed volatilization along with biodegradation of BTX compounds in a shallow aquifer and at gasoline spill sites, respectively. Recently, mass reduction by irreversible sorption was also reported by Baek et al (2003), who investigated the irreversible sorption of benzene using a column approach, showing that a significant amount of the added benzene was not desorbed from the same sandy material. Thus, volatilization coupled with irreversible sorption can be major processes affecting the fate of aqueous benzene during transport through the aquifer materials.…”
Section: Benzene Plume Movementmentioning
confidence: 81%
See 2 more Smart Citations
“…Baek et al [14] studied the benzene sorption in sand and conducted a test to verify the influence of Plexiglass ® in the results. In a separate experiment concentrations of benzene solution were measured with time for glass and Plexiglass containers under a closed system.…”
Section: Experimental Columnsmentioning
confidence: 99%